Crystallographic approach to fragment-based hit discovery against Schistosoma mansoni purine nucleoside phosphorylase. Issue 19 (15th October 2021) - Faheem, Muhammad; Fonseca Valadares, Napoleão; Brandão-Neto, José; Bellini, Dom; Collins, Patrick; Pearce, Nicholas M.; Bird, Louise; Roberta Torini, Juliana; Owens, Raymond; DMuniz Pereira, Humberto; Von Delft, Frank; Barbosa, João Alexandre Ribeiro Gonçalves
Abstract : Several Schistosoma species cause Schistosomiasis, an endemic disease in 78 countries that is ranked second amongst the parasitic diseases in terms of its socioeconomic impact and human health importance. The drug recommended for treatment by the WHO is praziquantel (PZQ), but there are concerns associated with PZQ, such as the lack of information about its exact mechanism of action, its high price, its effectiveness — which is limited to the parasite's adult form — and reports of resistance. The parasites lack the de novo purine pathway, rendering them dependent on the purine salvage pathway or host purine bases for nucleotide synthesis. Thus, the Schistosoma purine salvage pathway is an attractive target for the development of necessary and selective new drugs. In this study, the purine nucleotide phosphorylase II (PNP2), a new isoform of PNP1, was submitted to a high-throughput fragment-based hit discovery using a crystallographic screening strategy. PNP2 was crystallized and crystals were soaked with 827 fragments, a subset of the Maybridge 1000 library. X-ray diffraction data was collected and structures were solved. Out of 827-screened fragments we have obtained a total of 19 fragments that show binding to PNP2. Fourteen of these fragments bind to the active site of PNP2, while five were observed in three other sites. Here we present the first fragment screening against PNP2.